Use of “Kayod” Preparation in Cows - Luschai , Yulia; Dutova, Olga; Shaganova, Elena; Pleshakova, Irina; Mashkina, Elena (KnE Life Sciences, 2021)
The Altai territory is an agricultural region; it is a biogeochemical province deficient in iodine. We conducted a study of metabolic disorders in cows that had hypofunction of the thyroid gland. Our research is devoted to the expediency of a single use of the drug “Kayod” administered in the form of a subcutaneous implant in order to normalize the therapeutic status of animals suffering from a chronic lack of iodine in their diet. The purpose of this work is to justify not only the use of the preparation “Kayod” in animals kept in the biogeochemical provinces deficient in iodine, but also the use of tablets administered through a subcutaneous implant. We found a significant increase in the amount of hemoglobin and a decrease in the number of white blood cells in the blood of animals after the use of “Kayod”, and in the second experimental group, these indicators were slightly higher than in the first one. Indicators of the level of total protein and reserve alkalinity of blood were within the limits of physiological norms, but in the experimental groups they were slightly higher than in the control group. The level of total calcium and carotene in the blood of animals in the experimental groups, especially the second, significantly exceeded the level of the same substances in the blood of the animals in the control group. However, the level of inorganic phosphorus tended to decrease. The level of glucose in the blood of cows in the experimental group increased significantly more than in the blood of cows in the control group. This increase was particularly significant in the blood of animals in the second experimental group. When the preparation “Kayod” was used in the form of a subcutaneous implant, there were no clinical signs of hypothyroidism in the cows of the first experimental group after nine weeks. In the cows of the second experimental group, the condition of the cows returned to normal after six weeks. Keywords: Cows, iodine, hypothyroidism, implant, “Kayod